2016
DOI: 10.5194/isprs-archives-xli-b1-1011-2016
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach for Estimating Nitrogen Content in Paddy Fields Using Low Altitude Remote Sensing System

Abstract: Commission I, ICWG I/VbKEY WORDS: Low altitude remote sensing, Unmanned aerial vehicle, Rice, Vegetation index, Nitrogen ABSTRACT:Concerns over the use of nitrogen have been increasing due to the high cost of fertilizers and environmental pollutions caused by excess nitrogen application in agricultural fields. Several methods are available to assess the amount of nitrogen in crops, however, they are expensive, time-consuming, inaccurate, and/or require specialists to operate the tools. Researcher recently sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The soil properties included a 15% wilting point, 30.5% field capacity, and 42.9% saturation. The recorded bulk density was 1.40 g/cm 3 . Soil has a matric potential of 11.09 bar and a hydraulic conductivity of 57 mm/h [28].…”
Section: Site Description and Experimental Designmentioning
confidence: 97%
See 1 more Smart Citation
“…The soil properties included a 15% wilting point, 30.5% field capacity, and 42.9% saturation. The recorded bulk density was 1.40 g/cm 3 . Soil has a matric potential of 11.09 bar and a hydraulic conductivity of 57 mm/h [28].…”
Section: Site Description and Experimental Designmentioning
confidence: 97%
“…Plants absorb essential macronutrients such as phosphate ions (HPO 4 2− and H 2 PO 4 − ), nitrate (NO 3 − ), and ammonium (NH 4 + ). Pollution is known to occur when these elements discharge through leaching, mineralization, or volatilization, a situation that is further amplified through rapid degradation of the soil structure during the intensive rice cropping cycle [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In many instances, the nitrogen status is estimated indirectly from other variables, especially the chlorophyll content and leaf area index. Since the chlorophyll content is easier to measure than the nitrogen content (for example, using the SPAD device) [128], it is sometimes used as the target variable in investigations regarding remote nitrogen monitoring [110,117]. The problem with this approach is that the chlorophyll content may not be an accurate proxy of the nitrogen content if the concentration of the latter is high [111].…”
Section: Nutrition Disordersmentioning
confidence: 99%
“…Simultaneously, many recent studies [6][7][8][9][10][11][12][13][14][15][16][17] have demonstrated the capability of UAV based sensors to estimate common rice agronomics traits such as leaf or/and plant N content, the biomass of separate crop organs, yield components and other physiological responses that are useful for phenotyping studies. These traits are commonly used to evaluate the effects of fertilizers, irrigation management and weather on the rice crop growth development, either through field experiments or crop modelling [18][19][20] since they are direct indicators of rice growth and yield performance.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the results from past studies have illustrated that plant traits such as leaf or/and plant N content, biomass and yield could be inferred using various indices at different rice growing stages with good accuracy [6][7][8][9][10][11][12]. Fewer studies have been conducted for the rice leaf area index (LAI), plant height (PH), plant density and chlorophyll content [6,8,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%